HUBUNGAN PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATERI TEKS NARASI DI SDN 10 LANGSA - Fitria Annisa; Alpidsyah Putra; Juliati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low learning outcomes are caused by obstacles when students understand the material presented by the teacher, especially in the Indonesian Language subject. To avoid comparisons in learning achievement, teachers should provide instruction with diverse learning styles for all students in the class. Therefore, it is important for the author to determine